Pasarela para Usar Transmisores HART desde una Red DeviceNe - Barandica López, Asfur; Guevara Escobar, Andrés Ernesto (Ingeniería, 2015)
This paper demonstrates the feasibility of harmonizing two industrial protocols with very different characteristics, through the implementation of a hardware-software interface. HART is a very low speed protocol that operates with master-slave paradigm, connectionless oriented and with a defined set of commands, while DeviceNet is at least 100 times faster, works with the producer-consumer model, is connection-oriented and does not use commands but objects. The development is supported on the TINI (Tiny InterNet Interface) embedded system, which is Java programmable. The gateway acts as a slave on a DeviceNet network and as master of a HART network. This innovative equipment can be used to include HART devices in manufacture processes requiring few continuous variables.